Association between RANTES/CCL5 levels with Plasmodium infections and malaria severity: a systematic review - Pattamaporn Kwankaew; Aongart Mahittikorn; Wanida Mala; Kwuntida Uthaisar Kotepui; Nsoh Godwin Anabire; Polrat Wilairatana; Manas Kotepui (Malaria Journal)
Abstract Background Malaria continues to be a significant global health concern, and developing effective therapeutic strategies requires an understanding of the immune response to the disease. This systematic review synthesized the current body of research on the role of regulated on activation, normal T cell expressed and secreted (RANTES)—in the pathogenesis and disease severity of malaria. Methods A systematic review protocol was registered with PROSPERO under the registration number CRD42024535822. The systematic review was conducted following PRISMA guidelines to identify studies examining RANTES levels in individuals infected with Plasmodium species. Searches were performed across multiple databases, including ProQuest, Journals@Ovid, Embase, Scopus, PubMed, and MEDLINE. Further searches were performed in Google Scholar. Quality assessment was done using the Joanna Briggs Institute (JBI) critical appraisal tools. Alterations in RANTES levels in patients with malaria were synthesized narratively. Results A comprehensive search of major databases identified 22 studies meeting inclusion criteria, predominantly focusing on Plasmodium falciparum and Plasmodium vivax infections. RANTES levels were found to vary significantly across different severities of malaria, with several studies reporting lower levels in severe cases compared to non-malarial controls. However, inconsistencies were observed in the alterations of RANTES levels between severe and non-severe malaria cases. Conclusion Taken together, the finding of this systematic review underscore the complex regulation of RANTES in malaria pathophysiology. Future research should focus on longitudinal assessments to elucidate the dynamic role of RANTES throughout the course of malaria and recovery, to potentially inform the design of novel therapeutic strategies.